IR spectroscopy of a Pd-carbonyl surface compound - Libuda, Jörg; et al. (Chemical Physics Letters, 1997)
Pd is deposited onto a model alumina surface in the presence of ii CO atmosphere of 3 x 10(-6) mbar at liquid nitrogen temperatures-According to the LR spectra the palladium carbonyl compound formed contains weakly bound terminal and more strongly bound bridging CO molecules, the spectra being similar to the IR spectra of colloidal metal particles in solution and the IR spectra of CO adsorbed on small deposited Pd particles. In line with thermal desorption studies of the stability of the compound, the IR spectra reveal the transition from the compound to a situation where CO is adsorbed on larger compact metal aggregates upon heating to room temperature. (C) 1997 Elsevier Science B.V.